2018
DOI: 10.1186/s12906-018-2378-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial and cytotoxic activity of leaf extracts of Centella asiatica (L.) Urb, Warburgia salutaris (Bertol. F.) Chiov and Curtisia dentata (Burm. F.) C.A.Sm - medicinal plants used in South Africa

Abstract: BackgroundCompounds having both anticancer and antimicrobial activity have promising therapeutic potential due to their selective cytotoxicity and their potential to reduce the occurrence of bacterial and fungal infections in immune-compromised cancer patients. In our quest to find new antimicrobial agents with potent anticancer activity, the biological potential of leaves from the three medicinal plants Centella asiatica, Warburgia salutaris and Curtisia dentata as used by Zulu traditional healers for the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 41 publications
1
46
0
1
Order By: Relevance
“…However, drowsiness in doses between 1200 and 5000 mg/kg was reported [77] The compounds isolated from the methanol stem bark fraction (resveratrol derivatives) were reported to have low cytotoxicity on prostate cancer cell lines [78]. The ethanol root extract was reported to be nontoxic in brine shrimp larvae [74] [84] in vitro (Hole plate diffusion method, microdilution method) [83], in vitro (Bioautography assay) [84] The acetone leaf extract was reported to be cytotoxic against cancer cell lines [85] Carica papaya L.…”
Section: Diversity Of Medicinal Plants Identified In the Study Area Amentioning
confidence: 99%
“…However, drowsiness in doses between 1200 and 5000 mg/kg was reported [77] The compounds isolated from the methanol stem bark fraction (resveratrol derivatives) were reported to have low cytotoxicity on prostate cancer cell lines [78]. The ethanol root extract was reported to be nontoxic in brine shrimp larvae [74] [84] in vitro (Hole plate diffusion method, microdilution method) [83], in vitro (Bioautography assay) [84] The acetone leaf extract was reported to be cytotoxic against cancer cell lines [85] Carica papaya L.…”
Section: Diversity Of Medicinal Plants Identified In the Study Area Amentioning
confidence: 99%
“…De forma similar, outros estudos demonstraram que o lupeol apresentou atividade citotóxica para linhagens de câncer de mama, fígado e cólon, e pode se tornar um candidato promissor na terapia contra o câncer como medicamento, por causa da modulação na dinâmica mitocondrial, influenciando em processos que interferem na integridade da membrana, provocando apoptose. Contudo, será necessária ainda uma avaliação da posologia para aplicação em seres humanos em estudos posteriores, visto que os artigos apresentam ensaios in vitro e in vivo 28,84 .…”
Section: Discussionunclassified
“…The antimicrobial activities of extracts from the leaves and root of C. asiatica have been previously reported with MIC range of 10 to 20 mg mL À1 and 5 to >10 mg mL À1 . 46,48 As shown in Table 3, the green synthesized AgNPs demonstrated excellent antibacterial activity against the tested isolates with MIC of 0.625 to 1.249 mg mL À1 and MBC range of 2.498 to 9.994 mg mL À1 . The antimicrobial mechanisms of AgNPs are not elaborately understood, however it is suggested that the binding of the positively charge silver ions to the negatively charged bacterial cell wall components facilitates the penetration of the AgNPs across the membrane resulting in disruption of cell membrane, disintegration of DNA and interaction with cellular enzymes, transport proteins and other cytoplasmic components resulting in cell death.…”
Section: Antibacterial Activitymentioning
confidence: 92%